Analysis of Key Actors in the Sustainable Management of Marine Protected Areas in Ujung Kulon National Park - Suparyana Suparyana; Akhmad Fauzi; Tridoyo Kusumastanto; Gatot Yulianto; Muhammad Yusuf (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
The users or actors involved in the management of Marine Conservation Areas (MPA) in Ujung Kulon National Park (TNUK) come with various objectives, so it is necessary to always maintain the purpose of establishing a Marine Conservation Area in Ujung Kulon National Park (TNUK) so that it can be sustainable, both from the aspects of economic, social and ecology. The purpose of this study is to analyze the main actors in the management of Marine Conservation Areas in Ujung Kulon national park and formulate a sustainable conservation area management model based on these key actors. The research method is carried out with a survey approach by filling out a questionnaire. The respondents in the study were experts as many as 12 (twelve) people. The data analysis method used in this study is stakeholder analysis with the ISM (Interpretive Structural Modeling) method. The results of the analysis obtained by the main actors / stakeholders in the management of TNUK Marine Conservation Areas are: 1) Ujung Kulon National Park Center, Banten Provincial Bappeda, Communities (Fishermen), and Private Sector (Entrepreneurs). The proposed management model is a collaborative management model (Government-Community-Private).